Studi Komparasi Penambahan Massage Pada Strengthening Exercises Chronic Neck Pain - Alim, Wildan Asa, Wijianto SSt. FT. M. OR, Umi Budi Rahayu, S.Fis, M.Kes, Agus Widodo, S.Fis., M.Fis (2017)
Background: Human neck is a complex structure and is very prone to irritation. In fact, 10% of all people will experience neck pain within 1 month. Factors that cause pain include bones, muscles, ligaments, joints and intervertebral discs. The prevalence of neck pain in the adult population in Indonesia reached around 16.6%, with 0.6% experiencing neck pain advancing. Handling of non-pharmacological pain can be done by two methods, among others, strengthening exercise and yomeiho massage. This study aimed to compare the two methods of strengthening exercise and yumeiho massage in reducing pain neck pain. Methods: This study is a Quasi Experiment pre and post test with two group design. This study took place in the village office districts Klego Banyuurip village, and the village office village districts Blagung Simo Boyolali district in Central Java. The samples used in this study as many as 20 people. The data obtained were then tested using the Wilcoxon Rank Sum Test, while the second method to determine the effect on pain reduction Mann Whitney test was used. Results: Test the effect of the treatment group using the Wilcoxon I P = 0.002. Using the Wilcoxon test the effect of the treatment group II P = 0.004. Thus P <α (0.05) so Ho rejected, which means intervention treatment I and II gave a significant effect on pain reduction Chronic Neck Pain. Mann Whitney test to determine the differences of the two treatment groups, in which the treatment group I with a value of 1.1 Mean and Standard Deviation values of 0.60 and the second group with a mean value of 1.8 and standard deviation values for 0292 in order to get value P = 0.226, so P> α (0.05) which means that Ho is accepted that there is no difference in effect between group I and group II. Conclusion: The results showed Award Strengthening exercises with and without Massage can have a significant effect on pain reduction in Chronic Neck Pain. There is no significant difference between Strengthening exercises with and without massage to decrease chronic pain neck pain.